Non-marital Pregnancies and Unmarried Women's Search for Illegal Abortion in Morocco - Irene Capelli (Harvard FXB Center for Health and Human Rights, 2019)
Abortion in Morocco is illegal except to safeguard a woman's life or health. Morocco has put some sexual and reproductive health policies into motion that are in line with the standards defined by the World Health Organization and the United Nations Population Fund, especially after the 1994 International Conference on Population and Development, but Morocco's Penal Code continues to criminalize the practice. This paper explores how proposed reforms to the abortion law that on the surface seem to legalize abortion in cases of severe health disorders or rape in reality moralize abortion, since vulnerable women should prove these conditions through lengthy bureaucratic procedures. Drawing on ethnographic fieldwork on unplanned pregnancies, I examine the social and health inequalities surrounding illegal abortion. My results show that socioeconomic status, education, geography, and marital status all play a role in delineating which women are willing or able to obtain an abortion and under which conditions the abortion takes place. I use the concept of "reproductive governance" to examine the relevance of rights-based approaches in Morocco, ultimately arguing that the intersection of socioeconomic and political processes in the country normalizes the risk and occurrence of illegal abortion, particularly for unmarried women living in precarious socioeconomic conditions, who are not addressed by sexual and reproductive health policies.